Semiotic Analysis of The “Mandala” Symbol in The Film “Ketika Berhenti di Sini” as a Representation of The Process of Letting Go - Sri Purwati Pertiwi Kusumawati; Farida Nurfalah (Siber Nusantara of Law and Politic Review, 2026)
This study aims to analyze the representation of the mandala symbol in the film Ketika Berhenti di Sini as a visual construction of the process of letting go. The study employs a qualitative approach using media text analysis through Roland Barthes’ semiotic framework, which examines meaning at the levels of denotation, connotation, and myth. The analysis is further enriched by Stuart Hall’s theory of representation and Carl Gustav Jung’s analytical psychology to understand the construction of meaning and the psychological dynamics of the characters. The findings reveal that the mandala symbol functions as a system of signs that maps the transformation of the main character’s inner condition from imbalance, attachment, and denial toward the attainment of inner balance and self-wholeness (the Self). The shift in meaning associated with the north, west, south, and east directions represents the stages of the individuation process. Interview findings with filmmakers and audiences indicate that the mandala symbol serves as a narrative device that strengthens the representation of the character’s psychological dynamics while also opening spaces for diverse interpretations among viewers. This study contributes to the development of Indonesian film semiotics by integrating representation theory and analytical psychology in interpreting visual symbols as representations of characters’ psychological dynamics.